Seasonal and temporal evolution of nutrient composition of pastures grown on remediated and non remediated soils affected by trace element contamination (Guadiamar Valley, SW Spain) - Madejón, P.; Domínguez, M. T.; Murillo, J. M. (Spanish Journal of Agricultural Research, 2010)
Elevated trace element concentrations in soils can affect the solubility and uptake of essential elements, resulting in nutrient deficiencies in plant tissues. The present paper deals with nutrient composition of pastures established on polluted and remediated soils (Green Corridor of the Guadiamar river Valley), in order to check the potential nutritional disorders that could derive from the soil pollution. In addition, nutrient composition of a representative grass, Cynodon dactylon, collected in 1999 and 2008 was compared in remediated and non-remediated sites of the polluted area. In general, nutrient concentrations of pastures were similar or even higher in polluted sites compared to ’control’ sites. Therefore, the estimated potential ingestion of main nutrients by horses (the most abundant animals in the area) was also greater in the polluted and remediated soils and covered their nutritional requirements (more than 300 (N), 70 (S), 35 (P), 400 (K), 175 (Ca) and 30 (Mg) mg kg–1 body weight day –1 in spring and autumn). Temporal evolution of nutrients and physiological ratios (N/S, Ca/P, K/Na, K/Ca+Mg) in C. dactylon showed a significant variation from 1999 to 2008, especially in the non-remediated area, leading to a recovery of the nutritional quality of this grass. The reasonable nutritional quality of pastures and the absence of negative interactions between nutrients and trace elements seem to indicate a stabilisation of soil pollutants in the affected area.